A Comparative Study of ICT Programs in Basic Education in Australia, Finland and Iran - Marjan Kian (Comparative Education Society of Iran ( CESIR), 2019)
International assessments of information and communication technology (ICT) in educational systems show that some countries have made quick advances. This study aimed to investigate ICT policies and programs in the pioneering countries i.e. Australia and Finland and compare them to Iran. To analyze the data and present the results, George Bereday's method was used in four levels of description, interpretation, juxtaposition and comparison. The sample included the relevant documents that were purposely selected through the library and electronic resources. Data were analyzed by qualitative analysis of the documents. The findings showed that Australia's latest action is the National School Reform Agreement 2019-2023, which emphasizes the development of educational programs and curricula. Finland, as the first European country to initiate the integration of ICT in the educational system has been pursuing the development of future teachers' skills, designing e-learning, cultural preparation of schools and attracting business partners by launching the "ICT in School Everyday Life" initiative since 2010. Iran, along with its first efforts in designing programs such as Takfa, Roshd Network and Smart Schools, was able to accompany these developments. Overcoming challenges such as weak private sector participation, lack of long-term financial investment, lack of pre-service teacher training, and lack of coherent evaluation strategies can be a major step in the development of ICT programs in Iranian public education.